Studi Pemilihan Moda Transportasi Kereta Api Ekonomi Lokal Kertosono Dan Kereta Api Dhoho (Rute Surabaya – Kertosono) - Leny Jely Anggraini; Nugroho Utomo (Universitas Dr. Soetomo, 2023)
In Indonesia, services in the transportation sector are one of the things that must be considered. Transportation services and regulations will change over time. One example of proof of service changes, especially in this pandemic era, can be shown by PT. Indonesian Railways, which has implemented all trains using AC facilities, has restricted visitors from entering stations, implemented health protocols, and brought order to street vendors. From these changes, each mode of transportation, especially the local Economy Train Kertosono and Dhoho Train, has different characteristics in terms of travel time, fares, departure times, and others. Travelers will always have their own choice of transportation mode. To find out the probability value of the selected transportation mode, it is necessary to conduct a survey of the factors that will be reviewed by travelers who use the Kertosono Local Economy Railway and Dhoho Railway to Surabaya – Kertosono transportation modes by distributing questionnaires and using the Stated Preference method. Based on the results of research regarding the selection of transportation modes between the Kertosono Local Economy Train and the Dhoho Train which were analyzed using the Microsoft Excel program, significant results were obtained on the magnitude of the probability value of choosing a mode of transportation based on the difference in ticket prices of Rp. 2,000,- then the probability value of PKAD is 0.63 and the probability value of PKAE is 0.37. While the value of the probability of choosing a transportation mode based on the difference in travel time is -7, the probability value of PKAD is 0.65 and the probability value of PKAE is 0.35.